Implementasi Teknik Hibrida Enkripsi Aes Dan Steganografi Multi-Platform Pada Aplikasi Berbasis Web 'Steganoid' - Farid Kurniawan; Abdul Muzakky; Nuafal Aziz Mulyono; Ahmat Fahri Matondang (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2026)
In the era of massive digital information exchange, data security has evolved from mere encryption to the need for confidentiality regarding the existence of the data itself. This research report presents an in-depth analysis, design, and evaluation of SteganoID, a web-based steganography application developed to fulfill the requirements of the Cryptography and Steganography course at Universitas Malikussaleh (UNIMAL). The application integrates the Advanced Encryption Standard (AES) cryptographic algorithm with Least Significant Bit (LSB) steganography techniques and file structure modifications for image, audio, and PDF document media. This study explores the effectiveness of a hybrid approach in securing the text message